Laporan Kasus : Laki-Laki 52 Tahun Dengan Skizofrenia Paranoid - Sukma Mustika; Afrina Zulaikha (Lembaga Pengembangan Kinerja Dosen, 2025)
Schizophrenia is a serious mental illness that affects the way a person thinks, feels and behaves. People with schizophrenia seem to lose touch with reality, which can be distressing for them, their family and friends. The prevalence of schizophrenia according to Riskesdas in 2018 shows that the prevalence of schizophrenia is 6.7 per 1000 homes. The 52-year-old man was taken by his family because he was angry. The patient felt angry with his family why he was taken by his family to the hospital because the patient felt he was not crazy and had not hit anyone, then the patient spoke distractedly. The patient also said that he received whispers telling him to leave the house. The patient believes that all dead people will give strength to plants or all living creatures around the dead person's grave. Based on the history, physical examination and supporting examinations, the patient was diagnosed with F20.0 Paranoid Schizophrenia. Therapeutic management was carried out in the form of psychopharmaceuticals in the form of Risperidone 2x2mg and psychotherapy for the patient.